2009
DOI: 10.1679/aohc.72.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basic fibroblast growth factor on the development of the stem cell properties of human dental pulp cells

Abstract: in the presence of bFGF into immunocompromised mice revealed the formation of bone, cartilage, and adipose tissue. The donor hDPC-derived cells were labeled in the bone tissues located near the PLGA in the subcutaneous tissues of recipient mice using a humanspecific Alu probe. When cultured with a serum-free medium containing bFGF, the hDPCs strongly expressed STRO-1 immunoreactive products and sustained selfrenewal, and thus were almost identical in differentiation potential and proliferation activity to hDPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…The supplementation of b-FGF to culture medium enhanced the growth and proliferation of MSCs obtained from low-yield areas, such as dental pulp and synoviumderived stem cells (43,44). Interestingly, Bian et al (45) recently showed that peripheral blood of patients with bone sarcomas had higher numbers of CD105 + MSCs than did the peripheral blood of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of b-FGF to culture medium enhanced the growth and proliferation of MSCs obtained from low-yield areas, such as dental pulp and synoviumderived stem cells (43,44). Interestingly, Bian et al (45) recently showed that peripheral blood of patients with bone sarcomas had higher numbers of CD105 + MSCs than did the peripheral blood of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of BMP-7 induced early bone regeneration compared to scaffold hydroxyapatite/ polyamide (nHA/PA) only and scaffold with nontransduced BMMSCs [99] . Adenoviruses with Runx2 and fibroblast growth factor-2 have also shown to effectively enhance the osteogenic differentiation of stem cells [100,101] . Despite viral strategies promising effect on stem cell fate, non viral techniques have been employed to overcome the limitations of viral strategies including ransposons (mobile DNA elements), plasmids (circular, self-replicable double-stranded DNA), short-interfering RNA molecules (siRNAs), cell-penetrating peptides, or bacterial artificial chromosomes (DNA constructs) to deliver a transgene [102] .…”
Section: Delivery Of Genetic Clues For Stem Cellsmentioning
confidence: 99%
“…FGF-2 has diverse effects on the functions of cells, including migration, differentiation, integrin expression, and embryonic development. FGF-2 also promotes the proliferation of various types of cells such as vascular endothelial cells, chondrocytes, osteoblasts, and mesenchymal stem cells [40][41][42][43], while maintaining their multipotency [44]. In the present study, the activity of FGF-2 released from the hydrogel particles was determined by assessing the proliferation of osteoblast-like MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 89%